The effect of synthesis route on the photocatalytic performance of Ag-TiO2 using rhodamine b dyes, pesticides, and pharmaceutical waste as model pollutants - Emmanuel Nyankson; Nathaniel Yeboah; Samuel Ocrah Jnr; Sammy Onaja; Thomas Mensah; Johnson K Efavi (Materials Research Express, 2022)
The use of noble metal loading such as Ag to improve the photocatalytic performance of TiO _2 has been well studied. Though different synthesis methods have been used to synthesize Ag-TiO _2 nano-composite, the effect of the different synthesis routes on the photocatalytic performance has not been studied and compared. This study focusses not only on the enhancement of photocatalytic performance by the addition of Ag, but also on the influence of the synthesis process on photocatalytic performance. Two different routes: photodeposition (PD) and formaldehyde assisted microwave (MW) synthesis of Ag-TiO _2 nano-composite and their photocatalytic performance were evaluated using model pollutants. The Ag-TiO _2 were synthesized using different wt% (0.5, 1.0, 1.5 and 2.0 wt%) of Ag. The synthesized Ag-TiO _2 were characterized with x-ray diffractometer, scanning electron microscopy-energy dispersive x-ray spectroscopy (SEM-EDX) and UV–vis spectrophotometry. The Ag-TiO _2 photocatalyst showed superior photocatalytic performance towards rhodamine b dye as compared to raw TiO _2 . 0.5 wt% Ag-TiO _2 -PD recorded the highest rate constant and degradation percent among the composites synthesized using photodeposition (PD) method. On the other hand, 1.0 wt% Ag-TiO _2 -MW performed better among the composites synthesized using microwave and formaldehyde assisted synthesis. The potential of these best performing composites; 0.5 wt% Ag-TiO _2 and 1.0 wt% Ag-TiO _2 to photocatalytically degrade pharmaceutical (Naproxen Sodium and Flurbiprofen) and pesticide (Atrazine and Pyrimethanil) pollutants were examined. These composites degraded the pollutants exceptionally well with 0.5 wt% Ag-TiO _2 -PD outperforming the 1.0 wt% Ag-TiO _2 -MW. 1H NMR and 13C NMR analysis revealed that the synthesized Ag-TiO _2 were effective in degrading the model pollutants.